eZ-Bayan: an interactive website to learn science of al-Bayan - Awang Ali, Mohammad Amnan; Abdul Rahim, Abdul Hadi; Hussin, Muhammad Hafizuddin; Aminordin, Nor Amira; Engku Mohamed Nor, Engku Amir Hamzah (Association of Malaysian Muslim Intellectuals, 2020)
The purpose of this study is to help Arabic language learners at the Department of Arabic Language and Literature of International Islamic University Malaysia (IIUM) in learning ‘Science of al-Bayan’ by designing a prototype courseware for them. This study was conducted by using systematic descriptive and analytical methodologies, where the descriptive approach required the researcher to gather information about ‘Science of al-Bayan’ and theories of learning through an educational blog. In addition, there were several stages of scientific procedures in the analytical approach. First and foremost, learners’ needs analysis was conducted before the phase of design. Secondly, experts’ review analysis was conducted during the design phase. The next stage was the analysis of the results of pre- and post-tests done by learners. Lastly, the analysis of formative evaluation by the learners after the completion of the development phase was also conducted. A special prototype courseware in learning ‘Science of al-Bayan’ was designed by using an educational blog, based on ADDIE instructional design model in the design and development process based on students’ needs, opinions and suggestions. The participants of this study were 60 students (27 students were selected during the needs analysis phase and 33 students were chosen during the pre- and post-tests and also during the evaluation phase). Two experts were selected from the field of Computer Assisted Instruction (CAI) and Arabic Rhetoric during the needs analysis phase. The results of this study showed that the majority of the students were positive about learning ‘Science of al-Bayan’ through the educational blog which increased their learning desires and motivation, while at the same time improved their understanding and performance in learning this subject.